Trauma patients presenting to the emergency department of a tertiary care hospital - Thapa, Ashish; Parajuli, Roshan; Shrestha, Sunita; Shrestha, Rashmi (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Trauma is one of the major reasons for visiting the Emergency Department. Road Traffic Accidents, falls, occupational injuries and assaults are the most common causes. The incidence of trauma is increasing in Low and Middle Income Countries. This study aimed to find out the prevalence of trauma in patients visiting the emergency department in a tertiary care hospital in Western part of Kathmandu, Nepal.Method: After the ethical approval from the National Health Research Council, a retrospective study was conducted in patients with a history of trauma presenting to the Emergency Department of Nepal Armed Police Force Hospital, Balambu, Kathmandu, Nepal from May 2021 to November 2021. Demographic variables, time of incident, time of presentation to the hospital, site of injury and outcomes were recorded in Microsoft EXCEL and analysed using Statistical Package for the Social Sciences version 16.Result: Total of 153 patients with a history of trauma visited the Emergency Department during the study period. 66.66 % of patients were males. The mean age of the patients was 30.83 ± 17.55 years. Majority of the patients were from 20 to 40 years of age. Fall (59.47%) was the most common mechanism of injury followed by road traffic accidents (16.99%). 87.58% were from Kathmandu Valley. Most of the trauma occurred between 6 am to 6 pm, 83.66% patients were in this section. 43.80% of the patients presented within 30 minutes of incident. Extremity injuries (72.54%) were more common than other injuries. The length of stay in the majority of the patients was less than 6 hours.Conclusion: Falls and road traffic accidents are the most common causes of physical trauma. Young males are the vulnerable populations.